1999
DOI: 10.1183/09031936.99.13105399
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline induces a reduction in circulating interleukin-4 and interleukin-5 in atopic asthmatics

Abstract: Mast cells and eosinophils may play a role in the pathophysiology of chronic cough in nonasthmatics. It is unknown, however, whether degranulation of these cells occurs in the airways of such patients.Thirty-five nonsmoking patients referred with a chronic nonproductive cough (mean cough duration 76.2 months) were evaluated using a comprehensive diagnostic protocol. Bronchoalveolar lavage (BAL) cell differentials and BAL histamine, tryptase and eosinophilic cationic protein (ECP) concentrations were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…Two treatments are given in randomized order over several crossover periods, with masking of both the participant and the researcher [9,18]. Randomized, double-blind, placebo-controlled n-of-1 trials of nebulized recombinant human deoxyribonuclease (DNase) in cystic fibrosis (CF) were well suited to an n-of-1 design given the drug's rapid onset of action (within 5 days) and its short duration and carryover effects (most effects disappear within 10 days of cessation) ( Table 2) [9,15,19]. The study used two consecutive 14-day periods, with placebo or DNase randomly allocated to the first or second period.…”
Section: N-of-1 Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two treatments are given in randomized order over several crossover periods, with masking of both the participant and the researcher [9,18]. Randomized, double-blind, placebo-controlled n-of-1 trials of nebulized recombinant human deoxyribonuclease (DNase) in cystic fibrosis (CF) were well suited to an n-of-1 design given the drug's rapid onset of action (within 5 days) and its short duration and carryover effects (most effects disappear within 10 days of cessation) ( Table 2) [9,15,19]. The study used two consecutive 14-day periods, with placebo or DNase randomly allocated to the first or second period.…”
Section: N-of-1 Trialsmentioning
confidence: 99%
“…The study used two consecutive 14-day periods, with placebo or DNase randomly allocated to the first or second period. To address disease variability in CF, the 28-day assessments were repeated until two assessments either showed a response or no response (best of three assessments) [19]. Meta-analysis of individual n-of-1 trials can be used to estimate overall population effects [9,20], and effect sizes can approximate those of large RCTs [9].…”
Section: N-of-1 Trialsmentioning
confidence: 99%
“…[15][16][17] Indeed, different studies have shown a wide variation in the clinical response to rhDNase-I with about 30% of patients-the so-called non-responders-not benefiting from it. [18][19][20] The reason for the failure of rhDNase-I in these patients is not understood. This study was therefore undertaken to elucidate the reason for the failure of rhDNase-I in certain CF patients and to evaluate strategies to overcome this.…”
mentioning
confidence: 99%
“…30,31 ABD'nin KF Derneği, 6 yaş ve üzerindeki orta ve ağır akciğer hastalığı olan KF hastalarında, solunum fonksiyonlarının düzeltilmesi ve alevlenmelerin önlenmesi için dornaz alfanın kronik kullanımını güçlü bir şekilde öner-mektedir. 32 Beş yaş altında da iyi tolere edilmektedir. Dornaz alfa DNA miktarını azaltarak aminoglikozid antibiyotiklerin etkinliğini artırmaktadır.…”
Section: Tanı Amacıylaunclassified